Sistem Rekrutmen Tenaga Pendidik dalam Meningkatkan Profesionalitas Guru di MTs Salafiyah Syafi'iyah Tebuireng Jombang - Miftahul Ulum; Mahmud Fauzi (Menara Tebuireng, 2019)
By procuring or recruiting educators at an educational institution, it is expected that an educational institution will get employees both in number and quality according to needs, so that the HR functions within an educational institution can be carried out effectively and efficiently and are able to bring up professional educators. This study aims to find out about the Education Personnel Recruitment System that is managed and handled by the Quality Assurance Agency in the Field of School/Madrasah Development in Improving Teacher Professionalism in MTs. Salafiyah Syafi’iyah Tebuireng Jombang. In this study, there are three problems to be examined, namely: (1) How is the recruitment system for teaching staff in MTs. Salafiyah Syafi’iyah Tebuireng Jombang?. (2) How to improve teacher professionalism in MTs. Salafiyah Syafi’iyah Tebuireng Jombang?. (3) What are the factors that constrain teacher recruitment in MTs. Salafiyah Syafi’iyah Tebuireng Jombang?. This type of research is a qualitative field study by collecting data about the Recruitment System of Education Personnel in Improving Teacher Professionalism in MTs. Salafiyah Syafi’iyah Tebuireng Jombang, which is managed and handled by the Tebuireng Boarding School Quality Assurance Institute. The data collection techniques using interviews, observation, and documentation. Based on data collected repeatedly with domain data analysis techniques, the researcher checks the validity of the data with triangulation of sources and techniques and uses reference materials such as cameras and voice recording devices. The results showed: (1) Recruitment should not be a trivial matter for an educational institution, but the recruitment of educators should be full of effective and efficient planning. (2) The institution always strives to develop teacher competencies so that teachers become professional educators, such as by providing local training at least every two years, and including general training and Teacher Competency Test or teacher character assessment. (3) Evaluating the implementation of recruitment in order to find out the existing constraints, so that the right solution can be found